Arabic as a Source of Foreign Legal Reference: Its Relevance and Challenges in Legal Education in Indonesia - Ahmadi Ahmadi; Sri Warjiyati; Arief Budiono; Jamal Hi Arsad; Sultan Alwan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Arabic is one of the primary source languages for various international legal documents, bilateral treaties, and the legal systems of countries with Sharia-based or mixed legal frameworks. This article explores the relevance of Arabic language proficiency as a component of foreign legal literacy within legal education in Indonesia. Using a qualitative approach through literature review and curriculum analysis, the study finds that mastery of Arabic significantly enhances the comprehension of foreign legal texts, including international agreements, commercial laws, and transnational civil law. Nonetheless, several challenges persist, such as the lack of standardized teaching materials, inconsistencies in legal terminology, and the limited number of qualified instructors capable of integrating language and legal studies effectively. This study recommends the incorporation of legal Arabic into law school curricula, particularly in areas focusing on international law, comparative law, and legal translation